Systematic revision of the pantropical whip spider family Charinidae Quintero, 1986 (Arachnida, Amblypygi) - Miranda, Gustavo Silva de; Giupponi, Alessandro P.L.; Prendini, Lorenzo; Scharff, Nikolaj (European Journal of Taxonomy, 2021)
The whip spider family Charinidae Quintero, 1986 is the most speciose and widely distributed in the arachnid order Amblypygi Thorell, 1883. It comprises three genera and 95 species distributed across all tropical continents and the eastern Mediterranean. Despite recent advances in the taxonomy of the family, a global revision of all its species, necessary to advance understanding of its systematics, biogeography and evolution, has never been conducted. In the present contribution, the family is revised in its entirety for the first time, including all previous names and 33 new species, 24 in the genus Charinus Simon, 1892: C. alagoanus sp. nov., C. apiaca sp. nov., C. carinae sp. nov., C. carioca sp. nov., C. carvalhoi sp. nov., C. cearensis sp. nov., C. diamantinus sp. nov., C. euclidesi sp. nov., C. goitaca sp. nov., C. guayaquil sp. nov., C. imperialis sp. nov., C. loko sp. nov., C. magalhaesi sp. nov., C. miskito sp. nov., C. mocoa sp. nov., C. monasticus sp. nov., C. palikur sp. nov., C. perquerens sp. nov., C. puri sp. nov., C. renneri sp. nov., C. sooretama sp. nov., C. souzai sp. nov., C. susuwa sp. nov., C. una sp. nov.; eight in the genus Sarax Simon, 1892: S. bilua sp. nov., S. dunni sp. nov., S. gravelyi sp. nov., S. indochinensis sp. nov., S. lembeh sp. nov., S. palau sp. nov., S. rahmadii sp. nov., S. tiomanensis sp. nov.; and one in the genus Weygoldtia Miranda et al., 2018: W. consonensis sp. nov. Taxonomic keys to the 132 species (excluding four nomina dubia) are presented and several taxonomic rearrangements implemented. Four subspecies are elevated to species level: Charinus cavernicolus Weygoldt, 2006, C. elegans Weygoldt, 2006, C. longipes Weygoldt, 2006, and Sarax bispinosus (Nair, 1934). Sarax batuensis Roewer, 1962 is removed from synonymy with Sarax buxtoni (Gravely, 1915) and S. buxtoni newly synonymized with Sarax rimosus (Simon, 1901). Stygophrynus moultoni Gravely, 1915 is transferred to Sarax, resulting in Sarax moultoni (Gravely, 1915) comb. nov. Ten species are transferred from Charinus to Sarax, resulting in new combinations: S. abbatei (Delle Cave, 1986) comb. nov., S. bengalensis (Gravely, 1911) comb. nov., S. dhofarensis (Weygoldt, Pohl & Polak, 2002) comb. nov., S. ioanniticus (Kritscher, 1959) comb. nov., S. israelensis (Miranda et al., 2016) comb. nov., S. omanensis (Delle Cave, Gardner & Weygoldt, 2009) comb. nov., S. pakistanus (Weygoldt, 2005) comb. nov., S. seychellarum (Kraepelin, 1898) comb. nov., S. socotranus (Weygoldt, Pohl & Polak, 2002) comb. nov. and S. stygochthobius (Weygoldt & Van Damme, 2004) comb. nov.